The roles of proper data storage system of Bangladesh Bank Sanchayapatra bond holders in IFIC Bank Ltd - Tazwar, Kazi Muhtasim (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.